Gelatin speciation using real-time PCR and analysis of mass spectrometry-based proteomics datasets. (May 2018) - Jannat, Behrooz; Ghorbani, Kazem; Shafieyan, Hooshang; Kouchaki, Somaye; Behfar, Abdolazim; Sadeghi, Naficeh; Beyramysoltan, Samira; Rabbani, Faride; Dashtifard, Salman; Sadeghi, Mohsen
Abstract: Authentication of gelatin, an ingredient in food and drug products, is of interest with respect to some regulations and religion rules. Determination of the gelatin origin is particularly challenging because of the similarity in amino acid sequences of collagen types in different species. In this study, Polymerase Chain Reaction (PCR) technique using species-speciﬁc primers and also chemometrics analysis of mass spectral data were investigated to differentiate bovine, porcine and fish source of gelatin in commercial pure gelatin and gelatin-containing food and drug products. The specific PCR primer set was optimized using real-time PCR approach to routinely determine the gelatin source. Real-time PCR is sensitive to identify gelatin origin from traces of species-specific DNA. However, source determination is impossible when DNA is denatured or removed during production process. Alongside, chemometrics methods (PLS/DA and PCA) were used for mining LC/MS data sets to obtain patterns for discrimination of gelatin origins. LC/MS data sets involve MS spectrum of tryptic gelatin peptides generated from gelatin samples. Using PLS/DA method, a discrimination model is developed for identifying origin of the extracted gelatin. The method is practical to determine the halal authenticity of gelatin in the pure and processed products. Highlights: Real-time PCR using species primers was implemented for gelatin source detection. LC/MS data combined with chemometric methods to identify animal source of gelatin. Distinguishing bovine, porcine and fish gelatin in food and drug products.